2021
DOI: 10.3389/fonc.2021.689701
|View full text |Cite
|
Sign up to set email alerts
|

Rearrangements of Blood and Tissue Fatty Acid Profile in Colorectal Cancer - Molecular Mechanism and Diagnostic Potential

Abstract: Colorectal cancer (CRC) is often diagnosed at an advanced stage due to the invasiveness of colonoscopy; thus, non-invasive CRC diagnostics are desirable. CRC is associated with lipid alterations. We aimed to verify whether fatty acid (FA) profiles in CRC patients may serve as a potential diagnostic tool for CRC diagnosis. FA profiles were assayed by GC-MS in cancer tissue, paired normal mucosa and serum from CRC patients and healthy controls. The levels of very long FAs – VLCFAs (26:0, 28:0 and 26:1) were the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…The most important advantage of this study was further discovering and confirming the altered lipid metabolism in CRC tissue. The results partly confirmed our previous studies [11,21,28,67], but also provided a lot of new data. The advantage of this study was also using the matched tumor adjacent, micro and macroscopically normal colon mucosa and tumor samples from the same patients.…”
Section: Study Strengths and Limitationssupporting
confidence: 89%
“…The most important advantage of this study was further discovering and confirming the altered lipid metabolism in CRC tissue. The results partly confirmed our previous studies [11,21,28,67], but also provided a lot of new data. The advantage of this study was also using the matched tumor adjacent, micro and macroscopically normal colon mucosa and tumor samples from the same patients.…”
Section: Study Strengths and Limitationssupporting
confidence: 89%
“…Furthermore, we could not account for the effect of high heterogeneity of collected tissues and individual diversity among mice in our model, and this could greatly contribute to the outcome of our study. Indeed, it has been shown that principal component analysis does not show an unequivocal separation between cancer tissue and normal mucosa in CRC patients; paired comparison of cancer tissue and normal mucosa obtained from the same subject must be done to identify the difference [ 63 ]. Another potential explanation is that, in many cases, the patterns of non-significant differences in gene/protein expression or in the levels of metabolic intermediates as identified in the current study can lead to significant differences in the development of disease and, therefore, analysis of these patterns is as important as the identification of significant differences.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in HCC tumor tissue, most lipid groups were decreased in comparison to non-tumor hepatic tissue [45], which is intriguing, because other studies suggest enhanced FA biosynthesis in HCC tumors [51]. However, it has been proposed that in some other cancers, both FA synthesis and FA oxidation are stimulated at the same time [94,95], so this may be the case also in HCC. Another study showed increased percent of MUFAs and decreased PUFAs levels in HCC tumors compared to normal liver tissue [91].…”
Section: Hepatocellular Carcinoma and Lipid Alterationsmentioning
confidence: 94%